Evolution of the market process : Austrian and Swedish economics - Bellet, Michel, 1960-; Gloria-Palermo, Sandye; Zouache, Abdallah, 1959- (Routledge studies in the history of economics, 2005)
This impressive volume centres on the relationship between Austrian and Swedish economics. With themes such as capital theory, expectations, policy, market theory and the history of economic thought, it makes for an interesting read.